Innovative application of trapezoidal web profile section in steel construction - Mahmood Md. Tahir, 1962-; Arizu Sulaiman; Tan, Cher Siang, 1979-; Redzuan Abdullah; Conference on Integrated Solutions from Raw Materials to Final Products for Growth in the Steel Industry (2005 : Hanoi, Vietnam) (Skudai : Universiti Teknologi Malaysia, 2005)
09